A study model of a platform of cultural resistance. The catalán magazine Serra D’or : La revista catalana Serra D’or - Ferré Pavia, Carme (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
Considering the most relevant issues that in the Catalan social communication field had to be studied, the cultural magazine Serra d'Or seemed to be one of the most outstanding. This journal was a real intellectual platform of cultural resistance to dictatorial Franco's regime in Spain. Serra d'Or wanted to recuperate the Catalan culture, then prohibited, and provides for part of the results of the study that reveals a publication model as part of a collective intellectual. It bases on a part of the research results and reveals the role of the magazine as a witness of that time, a generational bridge, a cultural showcase and an element of modernity dissemination during the sixties and seventies. It stands beside other publications that have yet a preferential diagnosis in the history of communication.